Automation of Mathematical Modeling of Physical and Technological Processes in the Electronic Devices Manufacture - Nevliudov, I.; Chala, O.; Botsman, I.; Klymenko, O.; Vzhesnievskyi, M. (My University, 2021)
The variant of automation of the mathematical modeling process for forecasting the technological process parameters of manufacturing nano and microelectromechanical systems is proposed in the paper. For this task realization, a number of defects were identified and the causes of their occurrence were analyzed, as well as physical and technological transformations that occur in the substrates during technological processes. The software for automation of technological parameters forecasting process is developed and described.
Keywords: production; microelectromechanical systems; silicon substarte; software; defect